Discarding social investment and redistribution in the name of austerity? The case of Finnish family policy reforms 2007—2015. Issue 3 (3rd July 2019) - Nygård, Mikael; Nyby, Josefine; Kuisma, Mikko
ABSTRACT: Since the 1970s, Finland has conducted family policies that could be labelled social investments, for example, investments in work–family balance or public childcare, while at the same time it has protected the economic standard of families with children through various income transfers. However, after the 2008–2009 financial crisis these policies including those with socially investing objectives have been increasingly subjected to cuts in benefit levels and entitlements in order to lower public expenditure, which raises the question if there has been a shift away from social investments and redistribution towards austerity policies. By analysing government programs from the period 2007–2015, this article discusses if, and to what extent, such a change can be traced in the Finnish government discourse. More specifically the article studies the narrative stories used to legitimise changes (reforms) in existing family policy and to what extent these changes were informed by a social investment perspective focusing on 'new' social risks, a traditional redistribution perspective emphasising 'old' social risks, or a neoliberal austerity perspective advocating fiscal austerity and welfare cuts. We argue that the first two perspectives were dominant prior to and during the first phase of the international financial crisis, whereas the third perspective became dominant after the crisis. Moreover, the results show that the main storyline in the legitimisation of the reforms was stories of 'progress' in combination with stories of 'control' and helplessness'.